Optimalisasi Pelayanan Administrasi Melalui WEBDESAKU Menuju Smart Village di Desa Sirnamanah Kecamatan Darangdan Kabupaten Purwakarta - Nurhandayani, Nurhandayani; Helwani, Helwani; Marlina, Lina (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2024)
This Community Service aims to optimize administrative services through Webdesaku towards smart villages in Sirnamanah Village, Darangdan District, Purwakarta Regency. There are still several features that have not been filled in on the Webdesaku application, the uncertainty of village officials providing information on the Webdesaku application, the large number of Micro, Small and Medium Enterprises (MSMEs) that have not utilized Webdesaku to sell their products shows that Webdesaku is not yet optimal in supporting administrative services in village, so it is necessary to fill in empty features using assistance methods. The various letters issued by villages that have not been served via Webdesaku require a web-based village administration service system to be built in order to create a smart village. By assisting the implementation of a web-based village administration service system for the community and Sirnanah Village officials, we will be able to speed up the administrative service process in the village. The results of community service show that the Webdesaku features provided for Sirnamanah Village and the existence of a web-based letter request service are available. It is hoped that there will be follow-up on community service regarding the sustainability of the letter request service application and improvement of the application by adding an appropriate letter format.